Hydrocarbon Market in Countries with Developing Economy: Development Scenario - Kosov, Michael Evgenievich; Akhmadeev, Ravil Gabdullaevich; Smirnov, Vladimir Mikhailovich; Popkov, Sergey Yuryevich; Rycova, Inna Nikolaevna (International Journal of Energy Economics and Policy, 2017)
Hydrocarbon resources represent cumulative wealth of a country because they form for many millions of years. At the same time, the use of such resources is taking place all the time, from year to year. These two circumstances have predetermined two aspects of the hydrocarbon market research – a tactical aspect connected with the annual use by a country of its resources, and a strategic aspect connected with accounting for the remaining the raw material given exploration of new deposits. The undertaken study of the qualities of resource prices confirmed the synchronization effect of international countries-exporters’ losses because of unfavourable prices at the international raw materials markets. The scientific research offers to use indicators of tactical, strategic and integral dependence of a national economy on natural resources, taking into consideration the fact that emerging countries are multiresource producers. Taking a comprehensive strategic resource assessment of a country’s dependence as a basis, we are offering an order of weighing local resource characteristics, which, in turn, will help a wider practical use of monitoring of emerging countries’ resource dependence. Keywords: rÐµsource dependence of an economy, emerging states, development strategy, coal production, oil and gas exports, budget JEL Classifications: E6, F3